Bacteriocin production by rhizobia isolated from root nodules of Horse gram - Prabhavati, E; Anthony, JAM (Bangladesh Journal of Medical Science, 2012)
Thirty two Rhizobium strains were isolated from the root nodules of Horse gram plants grown in 32 soil samples collected from various regions in Andhra Pradesh, India. They were identified as rhizobia by nodulation test. These isolates were used to study the production of bacteriocins. All the isolates produced bacteriocins against the remaining isolates. The isolates HGR-4 and 9 showed maximum activity/inhibition zone among all the isolates, and also found to be inhibiting more number of isolates than that of other bacteriocin producing isolates. The bacteriocin protein substance produced by the isolates HGR-4 and 9 showed a molecular weight of 50 kDa by SDS-AGE and bacteriocin plasmids molecular weight is > 22 kb and > 24 kb. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9819 BJMS 2012; 11(1): 28-32